Studying Stimulant and Fungicidal Properties of Preparation“Argitos Agro” against Powdery Mildew in Greenhouse Conditions - Atсhemyan, L. H.; Mirzoyan, V. S.; Petrosyan, N. K.; Karapetyan, G. A. (ՀԱԱՀ հիմնադրամ)
“ Argitos Agro” is a plant growth stimulant with fungicidal effect and when disinfecting cucumber seeds and applying during the growing season, it does not have a significant effect on the development of powdery mildew disease. The preparation, indeed, has a stimulating effect on the germination of cucumber seeds, the growth of seedlings and plants, accelerates flowering, increases the yield and improves its quality indicators.
Keywords: Agronomy and Agroecology